Phenotypic compatibility among european pear cultivars and quince rootstocks Compatibilidade fenotípica entre cultivares de pereiras europeias e porta-enxertos de marmeleiro - Machado B.D.* (2015)
© 2015, Universidade Federal de Santa Maria. All rights reserved.The pear (Pyrus communis L.) crop offers an expansive market opportunity in southern Brazil, because of amicable climatic and soil conditions. However, the lack of studies on compatibility of european pear cultivars and rootstocks is one of the limiting factors on the development of the pear crop in southern Brazil. The use of quinces as rootstocks has the advantages of vigor reduction and earlier bearing trees. However, some of these combinations can present some incompatibility graft. The objective of this study was to evaluate phenotypicaly the morphological compatibility among european pear cultivars and quince rootstocks. The evaluated variable were the section increment of cultivars and rootstocks trunk diameter at the graft union; the diameter difference between scion and cultivars and rootstocks; ‘translocated’ incompatibility; ‘located’ incompatibility; and the vascular connection of the graft union by immersion of the base of the plants (under the graft union) in a 0.08% Fuccinic acid solution. The experiments were conducted in an european pear orchards in the region of Urupema municipality, state of Santa Catarina, during the 2011/12, 2012/13 and 2013/14 growing seasons. The european pear cultivars and rootstocks evaluated were: ‘Abbé Fetel’/‘Adams’, ‘Decana du Comice’/‘Adams’, ‘Clapp’s Favourite’/‘EMA’, ‘Rock’/‘Adams’, ‘Packham’s Triumph’/‘EMA’ and ‘Santa Maria’/‘Adams’. ‘The Clapp´s Favourite’/‘EMA’ combination showed a `located incompatibility by descontinued vascular graft region, preventing the dye translocation. ‘The Rocha’/‘Adams’ and ‘Abbè Fetel’/‘Adams’ combinations did not present graft incompatibility, showing continued vascular union and no vascular disruption between cultivars and rootstocks. The ‘Santa Maria’/‘Adams’, ‘Decana du Comice’/‘Adams’ and ‘Packham´s Triumph’/‘EMA’ combinations showed a good graft union region with clear and continued bark and wood bond lines. The ‘Clapp´s Favourite’/‘EMA’ combination showed high incompatibility and is not recomented for the experimental conditions evaluated. The ‘Abbè Fetel’/‘Adams’ and ‘Rocha’/‘Adams’ combinations showed the highest graft compatibility among cultivars and rootstocks and are the best recomended combinations. Additionly, the ‘Santa Maria’/‘Adams’, ‘Decana du Comice’/‘Adams’ and ‘Packham´s Triumph’/‘EMA’ combinations showed partial compatibility and can eventually be indicated for high and super plant density when ‘Abbè Fetel’/‘Adams’ and ‘Rocha’/‘Adams’ combinations are not available.